2015
DOI: 10.1111/1744-7917.12241
|View full text |Cite
|
Sign up to set email alerts
|

Protease inhibitors in Bombyx mori silk might participate in protecting the pupating larva from microbial infection

Abstract: Pupae inside cocoons rarely suffer from disease. It is apparent that some factors in the cocoon exert antimicrobial effects whereby the pupae inside can be protected from microbial infection. In the present study, we investigated the expression of cocoon protease inhibitors using immunoblotting and activity staining. Enzymatic hydrolysis of cocoon proteins in vitro was performed to characterize their roles in protecting the cocoon from microbial proteases. We found that some protease inhibitors, particularly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In addition, small amounts of trimer were also observed in some silkworm tissues, including the integument and haemolymph of the 3-day-old pupae. Furthermore, in our previous study, we found that large amounts of BmSPI39 could be secreted into the cocoon layer during the spinning process (Li et al, 2016b). In fact, BmSPI39 is quantitatively one of the most abundant protease inhibitors found in cocoon silk (Dong et al, 2013;Zhang et al, 2015;Guo et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In addition, small amounts of trimer were also observed in some silkworm tissues, including the integument and haemolymph of the 3-day-old pupae. Furthermore, in our previous study, we found that large amounts of BmSPI39 could be secreted into the cocoon layer during the spinning process (Li et al, 2016b). In fact, BmSPI39 is quantitatively one of the most abundant protease inhibitors found in cocoon silk (Dong et al, 2013;Zhang et al, 2015;Guo et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…However, the molecular masses of these trimeric and tetrameric forms of BmSPI39 were decreased dramatically at 108 h after the start of wandering (equal to the period of 2.5‐day‐old pupae). Notably, BmSPI39 protein also has a signal peptide of 24 amino acid residues (Li et al, ; ). Our data suggest that this N‐terminal signal peptide was removed from the pre‐mature BmSPI39 protein during the secretion process (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations